MULTI-METHOD ANALYSIS OF BRONZE AGE CERAMICS FROM SATU-MARE COUNTY, ROMANIA - NAGY, Emőke; GUTTMANN, Márta; MOLNÁR-KOVÁCS, Zsolt; BARABÁS, Réka (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Bronze Age settlements have been discovered in the region of river Eriu, Satu Mare County, Romania. This study includes the archaeometric examination of eight ceramic artifacts dated from the Early to the Middle Bronze Age, representing the Otomani culture. The used methods were petrography, scanning electron microscopy (SEM) equipped with energy-dispersive X-ray spectroscopy (EDX), X-ray powder diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR) and thermal analysis (thermal gravimetric analysis - TGA and differential scanning calorimetry - DSC). The study of archaeological ceramics needs an interdisciplinary approach, where scientific research can have an important role in supporting the archaeological study. Our aim was to support by scientific methods the archaeological assumptions, which describe the culture, their knowledge and opportunities. For this purpose, we wanted to select the most appropriate measuring methods and how can the measuring results complete each other for a complex description of the culture. Therefore, the evaluation methodology of the measurement data was given an increased importance. The selection of the samples depended on archaeological background, therefore, the samples allowed a case study for the testing of the measuring methods. The mineral-petrographic analysis included the approximation of firing temperature, identification of potential raw material sources, similarity between samples and the determination of the technology used. An additional objective was the establishment of usability for the testing methods to have accurate measurements. Loam from the region was also analyzed and compared with the results of the ceramic samples.